2004
DOI: 10.2148/benv.30.4.308.57151
|View full text |Cite
|
Sign up to set email alerts
|

Compact City and Urban Sprawl

Abstract: Both in Europe and North America there is a growing concern about the development of urban form, especially deconcentration of urban land use in the form of urban sprawl. This has unintentional consequences such as city centre decline, increased reliance on the use of the private car, and the loss of open space. While governments try to regulate the development of urban form, there are no easy solutions. However, policies such as 'new urbanism' and 'smart growth' in North America, and 'compact city' and 'mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
149
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(158 citation statements)
references
References 26 publications
1
149
0
8
Order By: Relevance
“…Previously, various planning efforts were made to curb suburbanization such as the "concentrated de-concentration" and "growth centers" policies in the 1960s and 1970s. These policies are generally assessed as having been successful in directing the growing population into certain growth centers and curbing urban sprawl (Dieleman and Wegener 2004). The Fourth Report on Physical Planning Extra (Ministry of Housing, Physical Planning and the Environment 1991), focused on channeling new urban (re)development to locations within the existing urban areas ("brownfield" locations) and new "greenfield" locations on the edges of existing cities (the so-called VINEX locations).…”
Section: History Of Railway Network Developmentmentioning
confidence: 99%
“…Previously, various planning efforts were made to curb suburbanization such as the "concentrated de-concentration" and "growth centers" policies in the 1960s and 1970s. These policies are generally assessed as having been successful in directing the growing population into certain growth centers and curbing urban sprawl (Dieleman and Wegener 2004). The Fourth Report on Physical Planning Extra (Ministry of Housing, Physical Planning and the Environment 1991), focused on channeling new urban (re)development to locations within the existing urban areas ("brownfield" locations) and new "greenfield" locations on the edges of existing cities (the so-called VINEX locations).…”
Section: History Of Railway Network Developmentmentioning
confidence: 99%
“…Moreover, urbanization-driven land-use change is one of the main causes of political and social conflicts at various scales (Plotkin, 1987). As underlined in recent studies, urban sprawl in the Mediterranean region is determining a transition from a polarized landscape in urban and rural areas towards a diffused and mixed pattern of urban and peri-urban areas that spreads over the available land consuming both agricultural and semi-natural areas with important ecological implications (Dieleman and Wegener, 2004;European Environment Agency, 2006;Salvati et al, 2012). By comparing the land-use structure observed in Rome in 1949 and 2008, the present study has shown a trend towards fragmentation of both agricultural and forest land-use classes driven by low-density dispersed urbanization together with a spatial rearrangement of land-use classes whose distribution appears less associated with the distance from the inner city than it was in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, urban sprawl is a common phenomenon throughout Europe and is expected to continue during the upcoming decades (Dieleman and Wegener, 2004;European Environment Agency, 2006;Kasanko et al, 2006;UNEP, 2010). Salvati et al (2013) hypothesized the existence of an homologation process influencing together composition, structure and spatial configuration of periurban landscapes due to the effect of diffused urban expansion in the originally compact, large city regions of the Mediterranean basin.…”
Section: Introductionmentioning
confidence: 99%
“…Aj napriek tomu, že chápanie pojmu komerčná suburbanizácia je značne nejednoznačné, v geografickej literatúre je často frekventovaný (Šveda, Križan, 2011). Vo všeobecnosti zahŕňa rozmanité prejavy suburbanizácie, ktoré nesúvisia priamo s rezidenčnou suburbanizáciou (Sýkora, 2002, Dielman a Wegener, 2004, Matlovič a Sedláková, 2004, Spilková a Šefrna, 2010. Podľa Matloviča (2004) komerčnú suburbanizáciu možno chápať aj ako pokračovanie rezidenčnej suburbanizácie presunom pracovných príležitostí a komerčných aktivít z centra mesta, ako i vznikom nových aktivít do okrajových mestských častí, čo môže v pokročilom štádiu rozvoja viesť k vzniku okrajových častí miest konkurujúcich pôvodnému jadru mestskej aglomerácie.…”
Section: Teoreticko-metodické Východiská Problematikyunclassified